The making of NKT cells - Gapin, Laurent (2008)
Natural killer T cells acquire their unique phenotype and characteristics during development in the thymus. Evidence suggests that the transcription factor PLZF has a unique function in the development of these cells and their acquisition of ‘innate-like’ characteristics.